PENYAMAKAN KULIT IKAN NILA, GURAME, KAKAP PUTIH DAN ANALISA KUALITAS FISIKNYA - Intansari, Winda; darmanto, YS; Swastawati, Fronthea (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
The purpose of the research was to determine the effect of different types of fish skin is Nila(K1), Gouramy (K2) and White Snapper (K3) to the physical quality chrome tanned fishskins, in order to obtain optimum results and can be set to produce fish skin leather.Experimental design used was Randomized Block Design (RBD) with three types of fish skintreatment. Parameter tests include tensile strength, elongation at break and softness test. Thedata were analyzed using ANOVA, continued with Honesty Significant Difference Test andLeast Significant Difference at the level of 95% and 99% (α 0.05 and 0.01). Results showedthat K1 and K2 exert a significantly different (p <0.05) on the tensile strength. K1, K2 andK3 were highly significant (p < 0.01) against elongation at break. The softness test ontreatment K1, K2 and K3 were not significantly different (p < 0.05). The experimental resultsshow that the tensile strength of the tanned skin K1, K2, and K3 respectively 1302.71 ±91.89; 1065.23 ± 108.93; 1240.83 ± 39.32 N/cm2. The elongation at break skin test of K1,K2, and K3 respectively 58.51 ± 1.07; 80.01 ± 1.55; 44.46 ± 1.52%. the softness test of K1,K2, and K3 respectively 4.30 ± 0.19; 4.93 ± 0.26; 4.33 ± 0.26 mm. Based on the results of research concluded that K1, K2, and K3 could potentially be used as a raw material oftanning leather and end product. The optimum fish skin leather and in accordance with SNI06-4593-1998 was K1.